Inguinal bladder hernia, a rare cause of inguinal herniation: Report of two cases - Aliou, Zabeirou Oudou; Somuah, Tenkorang; Anas, Belhaj; Alae Eddine, Aissaoui; Tarek, Souiki; Moulay Hassan, Farih; Karim, İbn Majdoub; Imane, Toughrai; Khalid, Mazaz (Journal of Surgery and Medicine, 2019)
Hernia surgery is the most frequent in visceral surgery. The bladder is rarely involved in groin hernia. This is when a diverticulum or a part of the bladder wall is incarcerated within the hernia. This affection is often asymptomatic. The diagnosis is made per-or post-operatively following complications. We report 2 cases of inguinal hernia involving the bladder in which the first case was diagnosed preoperatively whereas the second was diagnosed intraoperatively.